EMPOWERING HIGH SCHOOL TEACHERS' COMPETENCIES THROUGH DIGITAL TECHNOLOGY DESIGN PROGRAM FOR CREATIVE LEARNING IN JAKARTA - Hidajat, Flavia Aurelia (As-Sidanah, 2025)
This digital technology design program aims to improve the empowerment of high school teachers' competencies in Jakarta in developing digital teaching materials for more creative learning. Digital teaching materials are in the form of digital books that can be accessed openly by their students. This digital teaching book is designed with the CANVA application, where teachers can create digital books innovatively according to the concept of the material to be taught. The method used in this digital technology design program is offline training to develop participant skills. The training was conducted offline in Jakarta. The participants were 23 high school teachers in Jakarta. Implementing the digital technology design program resulted in three participant responses in the satisfaction questionnaire. Participants obtained new and original ideas to develop creative teaching materials or learning instruments. The atmosphere of the fun digital technology design program activities has been created well by the presenters. In addition, participants gain positive benefits from developing their competencies in developing creative digital teaching books after this activity. The questionnaire results showed that participants gained new ideas in developing digital books, with a percentage of 26.09% for the "strongly agree" criteria and 73.91% for the "agree" criteria. The digital technology design program has a positive impact on the empowerment and improvement of the competencies of high school teachers in supporting creative learning through innovative digital technology. Unlike other programs, this program is done with direct practice and assistance until the product is finished.